Sosialisasi dan Implementasi Media Ular Tangga Biologi Matematika untuk Meningkatkan Pembelajaran Aktif SMA Kristen Payeti - Ariesta Riupassa, Desly; Dunga Rima, Kornelia; Arinita Ina Kii, Rosalia; Tamu Ina, Susanti; Tamaela, Kevin (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Low student engagement and activeness in the learning process is often caused by less interactive learning media. This community service activity aims to implement the